Measuring the Reliability of Postural Sway Measurements for a Static Standing Task: The Effect of Age - Lo, Pei-Yi; Su, Bo-Lin; You, Yu-Lin; Yen, Chen-Wen; Wang, Shih-Ting; Guo, Lan-Yuen (Frontiers in Physiology, 2022)
Background: The use of force plate to examine balance ability is common. However, only some medical centers or laboratory equipped with force plate due to the cost. Hence, a low-cost force plate can be easily applied to home care or health care institute. Nevertheless, few studies compared the reliability differences among age in postural sway measurements by a novel-designed and low-cost force plate for choosing reliable parameters to evaluate postural sway. Objectives: To investigate the reliability of a novel-designed force plate, and the age-effect on the test-retest reliabilities of the center of pressure (COP). Methods: Forty participants enrolled in this study, 20 youth and 20 elders, respectively. Participants were instructed to stand on the novel-designed and the low-cost force plate with static standing in eyes-opened and eyes-closed to measure the COP-related parameters. The within day test-retest reliability were examined at the two sessions on the same day, and the between days reliability were measured at two different days. The COP-related parameters included average velocity of COP, average velocity in antero-posterior and medio-lateral directions, mean distance of COP, mean distance in antero-posterior and medio-lateral directions. The intra-class correlation coefficient test was used to examine the test-retest reliability. Results: The novel-designed and low-cost force plate demonstrated excellent reliability on the COP velocity related parameters in within- and between-day measurements, meanwhile, the COP distance related parameters are good to excellent reliabilities in between-day measurements (range: 0.43 to 0.84). Elders demonstrated excellent reliability in mean distance of antero-posterior and that was higher than the youth participants in both eyes-opened and eyes-closed conditions. The reliability of mean distance of medio-lateral in elders was poor to good reliability (range: 0.38 to 0.55), while, that was excellent reliability in the youth participants. Conclusion: The novel-designed and low-cost force plate is reliable in measuring balance and the age effect existed for the reliability among different COP variables, hence, this study provided suggestions for the selection in COP measures.